The Impact of Cooperative Integrated Reading and Composition (CIRC) and Individual Learning Methods on Social Science Achievement among Junior High School Students - Siti Maesaroh; Atin Suprihatin (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: The rapid advancement of technology has increased smartphone usage among school-aged children, potentially affecting their academic motivation and focus. This concern has prompted investigations into the relationship between smartphone use and learning behavior, particularly in elementary education. Objective: This study aims to determine whether limiting the use of smartphones has an impact on students’ learning interest in elementary schools. Method: The study employed an ex post facto research design. It was conducted at SDI Daar Al Iman in 2021, involving a sample of 31 students. Data were collected using scales measuring smartphone use restriction and learning interest, then analyzed using simple linear regression. Result: The t-test results showed a significance value of 0.000, which is less than the alpha level of 0.05 (0.000 < 0.05). This indicates that limiting smartphone use has a significant effect on students’ interest in learning. Conclusion: The study concludes that restrictions on smartphone usage positively influence students' learning interests at school, suggesting that smartphone management can be an effective strategy to enhance academic engagement. Contribution: The findings provide practical and theoretical insights for teachers, educational practitioners, and future researchers. They highlight the importance of regulating smartphone use as a novel approach to support and sustain students’ learning motivation in the classroom.